The drug crisis in Iraq and its family, societal and psychological repercussion (Entrepreneurship Journal for Finance and Business, 2024)
For any phenomenon, whether it is bad or good, there are several causes that lead to it, and these reasons may refer to the individual in himself sometimes, or the society in its general composition and its total particles at other times, as it encourages the existence of this phenomenon, which means here that the phenomenon has an individual basis. Or social harm is harmful to the individual and society, and therefore it is necessary to search for means of combating it or addressing it and reducing its effects and risks, both individual and social, and striving to eliminate this danger once and for all.Rather, other economic, political and cultural efforts, especially the media, have an important role in combating or ending this phenomenon and its negative effects on society in general. Therefore, the drug phenomenon has causes that lead to it, and based on this is the need for different means and ways to combat this phenomenon, which in turn is diverse. It can be said that the reasons for giving drugs are limited to a group of reasons that belong to the individual in particular and constitute an important factor in pushing him to take drugs or become addicted to them.